2014
DOI: 10.7783/kjmcs.2014.22.5.391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Irrigation of Sulfur Solution before Sowing on Growth and Root Rot Disease of Seedling in Ginseng Nursery

Abstract: : To control the disease of root rot in ginseng nursery, inorganic sulfur solution of 0.1%, 1.0%, and 2.0% were irrigated by amount of 10 ℓ per 3.3 ㎡ before sowing. On the last ten days of July, Fusarium solani and F. oxysporum were similarly detected by 44.8% and 43.8%, respectively, while Cylindrocarpon destructans was low detected by 4.4% in the diseased seedling. The more sulfur's concentration was increased, the more soil pH was decreased. Soil pH was decreased from 5.87 to 4.59 by the irrigation of sulfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Kim et al (2018) have shown that paper disk containing loess-sulfur on PDA medium has antifungal activities against Colletotrichum gloeosporioides known to cause anthracnose in jujube. Also, inorganic sulfur compound on PDA media added with an inorganic sulfur has a distinctive growth inhibition effect on Cylindrocarpon destructans and Fusarium solani known to cause root rot in ginseng plant (Lee et al, 2014b). Furthermore, mycelium growth of Fusarium oxysporum causing vascular wilts in various plants is decreased on PDA medium added with sulfur nanoparticles (Choudhury et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al (2018) have shown that paper disk containing loess-sulfur on PDA medium has antifungal activities against Colletotrichum gloeosporioides known to cause anthracnose in jujube. Also, inorganic sulfur compound on PDA media added with an inorganic sulfur has a distinctive growth inhibition effect on Cylindrocarpon destructans and Fusarium solani known to cause root rot in ginseng plant (Lee et al, 2014b). Furthermore, mycelium growth of Fusarium oxysporum causing vascular wilts in various plants is decreased on PDA medium added with sulfur nanoparticles (Choudhury et al, 2011).…”
Section: Resultsmentioning
confidence: 99%